PENGARUH KOMPETENSI PENGELOLA KEUANGAN DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN - Hanifa, Lia; wawo, andi basru; husin, Husin (Pascasarjana Universitas Halu Oleo, 2016)
This study aimed to determine the effect of financial management competence andlocal finance accounting system on the quality of financial report at SKPD of the province ofSoutheast Sulawesi.The study used primary data garthered using a questionnaire.Respondents of the study ware structural officials and apparatus which run accountingfunction or financial management in 41 SKPD in the province of Southeast Sulawesi.Variables of the study included competence in financial management and the accountingsystem of local finace, which were independent variables, and the quality of financial reportsas dependent variable.Data analysis used a method of multiple regression statistical analysis using the SPSSversion 22 software, which were explained using descriptive statistics and inferentialstatistics. Result of hypothesis testing showed that the competence of financial managementand the accounting system of local finance have positive and significant effect on the qualityof financial reports written by the provincial government of Southeast Sulawesi, eitherpartially or simultaneously. It means that the better the competence of financial managementand the accounting system of local finance, the better the quality of financial reports that areproduced.Keywords: quality of financial repors, competence of financial management, accountingsystem of local finance..